Effect of Site‐Specific Peptide‐Tag Labeling on the Biocatalytic Properties of Thermoalkalophilic Lipase from Geobacillus thermocatenulatus. (4th January 2018) - Romero, Oscar; de las Rivas, Blanca; Lopez‐Tejedor, David; Palomo, Jose M.
Abstract: Tailor‐made peptides were investigated for site‐specific tag labeling of Geobacillus thermocatenulatus lipase (GTL). GTL was first genetically modified by introducing a unique cysteine on the lid site of the enzyme to produce two variants (GTLσ‐A193C and GTLσ‐S196C). Chemical modification was performed by using a small library of cysteine‐containing peptides. The synthesized peptide–lipase biocatalysts were highly stable, more active, more specific, and more selective toward different substrates than unmodified GTL. Very high enzyme thermostability of GTLσ‐A193C modified with peptides Ac‐Cys‐Phe‐Gly‐Phe‐Gly‐Phe‐CONH2 (1 ) and Ac‐Cys‐Phe‐Phe‐CONH2 (2 ) (>95 % activity after 24 h at 60 °C) was observed. The incorporation of1 and2 in GTLσ‐S196C improved its catalytic activity in the hydrolysis of p ‐nitrophenyl butyrate by factors of three and greater than five, respectively. The specificity for short‐chain versus long‐chain esters was also strongly improved. The diacylglycerol activity of GTLσ‐S196C was enhanced more than tenfold by the incorporation of1 and more than threefold by modification of this variant with Ac‐Cys‐(Arg)7 ‐CONH2 (6 ) in the hydrolysis of 1‐stearoyl‐2‐arachidonoyl‐ sn ‐glycerol. The enantioselectivity of GTLσ‐S196C increased for all formed bioconjugates, and the GTLσ‐S196C–1 conjugate was the most active and selective in the hydrolysis of dimethylphenyl glutarate at pH 7 (72 % ee ), also showing an inversion in the enzyme enantiopreference. Abstract : New semisynthetic lipases : Site‐specific chemical incorporation of cysteine‐containing peptide tags on the lid site of cysteine‐genetically modified thermoalkalophilic lipase variants is developed. New modified peptide–lipase conjugates with improved activity, specificity, and selectivity are prepared.